1989
DOI: 10.1016/0020-7292(89)90839-4
|View full text |Cite
|
Sign up to set email alerts
|

Severe abruptio placentae — still unpreventable

Abstract: The management of abruptio placentae remains a problem, despite advances in medical science. This study analyses severity of abruption, resultant morbidity, and maternal and fetal mortality in 105 cases. Among the contributory factors, hypertension (44%) and grand multiparity (24%) were common. There was no maternal death among these cases, mainly because of liberal use of blood transfusion, prompt delivery, and careful fetal monitoring, but perinatal mortality remained high (73%). Factors responsible for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 5 publications
0
19
0
2
Order By: Relevance
“…La survenue de l'HRP dans un contexte hypertensif est relevée par beaucoup d'auteurs [1,27,29,30]. Elle est illustrée par la fréquence de la toxémie gravidique parmi les facteurs de risque dénombrés dans notre série (près de la moitié des patientes [49,2 %] avaient une toxémie gravidique).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La survenue de l'HRP dans un contexte hypertensif est relevée par beaucoup d'auteurs [1,27,29,30]. Elle est illustrée par la fréquence de la toxémie gravidique parmi les facteurs de risque dénombrés dans notre série (près de la moitié des patientes [49,2 %] avaient une toxémie gravidique).…”
Section: Discussionunclassified
“…Dans la littérature, les taux varient de 12 à 86 % [2][3][4]8,21,30,36]. Le caractère imprévisible de l'HRP et les conditions d'admission des patientes influencent beaucoup le pronostic périnatal.…”
Section: Discussionunclassified
“…Our study shows that 69.11% cases were unbooked, Rai et al (1987) also reported more number of abruptio placentae cases were unbooked in his study. 6 The importance of antenatal visits in prevention of abruptio placentae has also been stated by Baskette et al (1977) who reported that in their series 3/4 th (75%) of cases were unbooked. 7 Increasing age has been implicated as a predisposing factor to both Placenta praevia and Abruptio placentae.…”
Section: Discussionmentioning
confidence: 76%
“…In abruption placenta group, Couvelaire uterus was seen in 2 (3.6%) cases. Rai et al (1981) 6 reported Couvelaire uterus in 10.5% of Antepartum haemorrhage patients in their study. One maternal death occurred in present study giving a maternal mortality of 1 in Antepartum haemorrhage patients.…”
Section: Maternal Outcomementioning
confidence: 74%
See 1 more Smart Citation